a) Phương trình 1,5x2 – 1,6x + 0,1 = 0
Có a + b + c = 1,5 – 1,6 + 0,1 = 0 nên x1 = 1; x2 = \(\dfrac{0,1}{15}\)
c) \(\left(2-\sqrt{3}\right)x^2+2\sqrt{3x}-\left(2+\sqrt{3}\right)=0\)
Có \(a+b+c=2-\sqrt{3}+2\sqrt{3}-\left(2+\sqrt{3}\right)=0\)
Nên x1 = 1, x2 = \(\dfrac{-\left(2+\sqrt{3}\right)}{2-\sqrt{3}}\) = -(2 + \(\sqrt{3}\))2 = -7 - 4\(\sqrt{3}\)
d) (m – 1)x2 – (2m + 3)x + m + 4 = 0
Có a + b + c = m – 1 – (2m + 3) + m + 4 = 0
Nên x1 = 1, x2 = \(\dfrac{m+4}{m-1}\)
a) Phương trình 1,5x2 – 1,6x + 0,1 = 0
Có a + b + c = 1,5 – 1,6 + 0,1 = 0 nên x1 = 1; x2 =
b) Phương trình √3x2 – (1 - √3)x – 1 = 0
Có a – b + c = √3 + (1 - √3) + (-1) = 0 nên x1 = -1, x2 = =
c) (2 - √3)x2 + 2√3x – (2 + √3) = 0
Có a + b + c = 2 - √3 + 2√3 – (2 + √3) = 0
Nên x1 = 1, x2 = = -(2 + √3)2 = -7 - 4√3
d) (m – 1)x2 – (2m + 3)x + m + 4 = 0
Có a + b + c = m – 1 – (2m + 3) + m + 4 = 0
Nên x1 = 1, x2 =